English article acquisition by Chinese learners of English: An analysis of two corpora. (August 2018) - Leroux, William; Kendall, Tyler
Abstract: The English article system presents a particular challenge to learners. This paper explores the acquisition of articles by Chinese learners of English in two corpora: one of Asian college EFL students, and one of Chinese professionals living and working in the United States. It seeks to describe patterns of L2 English articles across different proficiency levels. Our results show a surprising level of conformity of accuracy rates across participant proficiency levels. L2 speakers use articles in the most native-like manner in plural contexts. Certain errors are common, such as overusing the zero article in inappropriate contexts. Other errors are nonexistent, such as using more than one determiner in a noun phrase. In the end, we emphasize the importance of educators examining their students' L2 article use with an eye towards the commonly made errors that we uncover. In addition, we advise that L2 article patterns might appear grammatical, but still represent an oversimplified understanding of the English article system. We also suggest further topics for research in L2 acquisition of the noun phrase.